A critical analysis of the poetic discourse of Ihab Al-Shalabi; Ayyar's poem wakes me up at the sixtieth hour according to the method of Laclue and Mauve - Massud Fekri; Allibagher Taheriniya; Hossin Elyasi; Zeinab GhasemiAsl (دراسات في اللغة العربيّة وآدابها)
Critical discourse analysis is a new cognitive field for challenging and exploring discourse and is a tool to achieve a full understanding of discourse, which is done by entering the hidden aspects of the text using the means and methods of analysis. The importance of critical discourse analysis lies in the fact that it integrates discourse analysis with the study of the environment that creates discourse and examines the dialectical relationship between discourse and power, and thus is an attempt to determine the ideological approach of discourse. Numerous theories have been proposed for critical analysis of discourse and related approaches, and analysts in this field, relying on a set of approaches and basic mechanisms for the final and ideal cognitive realization of this analysis, focus on the study of discourse. Norman Fairclough developed the study of critical discourse analysis by proposing contextual theory, and Laclau and Moff's critical approach is the most important approach to critical discourse analysis. The main feature of this approach is to study the roots of discourse and focus on the signs and the process of marginalizing, highlighting and crystallizing. Commentary on the study of the poetry of Ehab Shelby in this article, which critically examines the ode "Ayar Yuzhani"; The poet composed this poem on the sixth anniversary of its defeat in 2008, and the results of the research indicate that this poem is full of fragmented and floating signs that depict the negative realities of the Arab society and political conditions, and the purpose of these signs is to expose that it is a critical reality, and the centrality of its central meaning and articulation revolves around the axis of resistance, uprising, and the emphasis on the weak presence of Arab society in two different dimensions. Just as the poet marginalizes another alien and an isolated Arab who opposes uprising and mobility, he highlights the motivation and current that opposes it, by crystallizing the practice of confrontation and focusing on the sacred act of history that it can repel and expel the enemy, it does. In this regard, the contemporary Jordanian poet marginalizes another usurper and institutionalizes and emphasizes the right of the Palestinian people, denies the occupation of the land and the humiliation of its rightful owners, and ignores the Palestinian issue and the weak position of the Arab rulers Condemns occupation and rape.